Persepsi Sosial Terhadap Komodifikasi Tubuh Perempuan (Studi Kasus Sales Promotion Girl Di Mall Ratu Indah Makassar) - Rusni Hadji; Nurdin Nurdin; Lukman Ismail (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2020)
Public spaces such as malls and entertainment venues have been visited by many people. This opportunity is used by industries engaged in the service sector to make a profit. Not a few agencies have created jobs to recruit employees in the field of promotional services. Promotion services work in the informal sector with the skills required by agencies to recruit women as sales promotions. SPG is used as a shortcut for some women to get a job. Women have a gentle attitude and are good at seducing with their physical capital, beautiful faces and eloquence in offering products to customers. SPG is used as the main job for women to make it easier to earn money. Most of the women who only go to school until they finish Senior High School (SMA) or Vocational High School (SMK) choose to work as SPGs. This job does not require high skills, only with a beautiful physique and face. This gives the view that the body and face are working capital as an SPG. The company benefits more from the SPG because it is seen as being able to boost product sales. In this study, the type of research used is a qualitative approach, namely "a research procedure that produces descriptive data in the form of writing and behavior that can be observed from the subject itself. The results of this study are 1) The concept of the body as a commodity is a common symptom in Makassar City. The body is likened to a commodity that has a selling value. As a commodity, the body can be converted just as the concept of the body is physical capital which can be converted into economic, cultural and social capital; 2) Some people view the SPG profession as a negative profession. because seen from the symbols attached to the SPG, for example, from wearing sexy clothes, make-up, to more aggressive and coercive verbal language when offering products and also the profession of SPG is a profession that only relies on beauty; 3) Negative stereotypes have been embedded in some societies so that what the general public perceives about SPG is almost the same.